Chemometric tools for a better understanding of fatty acid profile of fishes with potential to diversify fishing farming activity (Research, Society and Development, 2022)
This article evaluates the lipid profile of three fish species with the potential for breeding and diversification in Brazil and worldwide by means of chemometric tools. Grass carp (Ctenopharyngodon idella), Pacu (Piaractus mesopotamicus), and Catfish (Ictalurus punctatus) were captured at 24 months of age and analyzed for lipid profile using gas chromatograph. The multivariate analysis, discriminant and canonical discriminant, were used to better understand the differences in the lipid profiles between the three fish species. The fatty acid profile indicated oleic acid as the major component for all three species, resulting in a high percentage of monounsaturated fatty acids (MUFA). The Pacu presented the lowest content of polyunsaturated fatty acids. Discriminant analysis proved to be an important tool to differentiate lipid profiles between species. The pentadecylic (15:0), palmitoleic (16:1), margaric (17:0), stearic (18:0), arachidonic (20:4), and lignoceric (24:0) fatty acids presented the highest level of discrimination between species. This propagation of fatty acid values from these species reinforces their food quality and expands the possibilities of developing fish farming.